Exploration of Kompas Editorial Frames on Human Rights Issues during 2014-2021 - Yustitia, Senja; Ashrianto, Panji Dwi (Universitas Ahmad Dahlan, 2022)
Editorials occupy a vital position in the media because they present official media opinions to the public on specific issues, including human rights issues. Therefore, this study focuses on how Kompas daily frames editorials on human rights issues in January and December 2014–2021. The research method is qualitative with Urs Dahinden framing analysis techniques. This technique divides the typology of frames into five things: conflict, economy, progress, moral, and episodic. Dahinden's framing approach is interesting because it differentiates between issues and frames. January and December 2014-2021 were selected because this research does not focus on specific issues. January is a critical moment to reflect on human rights issues over the past year and the next. In addition, December is the month of commemoration of International Human Rights Day. The study results conclude that Kompas uses two different frames in its editorial related to human rights issues. In civil and political human rights, Kompas consistently uses a moral frame. Meanwhile, Kompas uses episodic, economic, and moral frames on economic, social, and cultural issues.